Hegelian Phenomenology and Meaningfulness of Life - Meysam Sefidkhosh (حکمت و فلسفه, 2014)
Hegel defines phenomenology as the knowledge of experiencing awareness. The ultimate goal of this field of study seems to be establishing that philosophy is a science by conceptually ‘phenomenalising’ the necessary steps to be taken in this course. Phenomenological establishment of the idea that philosophy is a science will involve phenomenological settling of a key question which has at least three sub-questions, one of which is the question of meaningfulness of life. In its complicated course of growth and development, awareness is depicted as a traveller who is broadening his experiences, who uses these experiences to critically survey his nature, meaning, course and goal, and who, acknowledging his weaknesses, continues his journey to overcome them. The journey on the whole is about finding the true meaning through developing into the ultimate awareness. Meanwhile, however, concepts like meaninglessness, absurdity and the like are among the many waypoints through which awareness navigates, at least as a swift pass, to reach the destination. The present paper considers the multi-layered course of the history of the Hegelian phenomenology to look at it within the domain of the concept of meaningfulness of life, providing a new reading of the phenomenological journey of awareness as it would relate to that concept. The paper raises the question as to whether a different approach than the one adopted by Hegel in his Philosophy of Right can be used to settle the question of meaningfulness of life. Making an affirmative response, the paper then claims that the Hegelian phenomenology is in fact an escape route from Jacobean critiques of the Kantian-Fichtean nihilism. The paper addresses the question of meaningfulness of life from two aspects based on Hegel’s Philosophy of Spirit: one is the value of life in general, and the other the ethical and social values which are contained in the value general value of life and guarantee it.